Comparative analysis of the composition of intestinal microbiome in patients with liver diseases - Martynov, Vladyslav; Havryliuk, Viktoriia; Skliar, Tetiana; Sokolova, Iryna (ScienceRise: Biological Science, 2020)
Aim: to analyze the composition of the intestinal microbiome in patients with liver diseases of various etiologies. Materials and methods: 128 patients of different sexes with pathological liver lesions were examined. The diagnosis of diseases was carried out using laboratory and instrumental methods of research. The study of the composition of microbiota in qualitative and quantitative indicators was carried out using standard bacteriological methods. The statistical analysis was performed using Student’s t-test. Differences in indicators were considered significant at P<0.05. Results: the comparative analysis of the composition of the intestinal microbiocenosis of patients with various liver diseases showed significant drops in the titers of symbiotic bacteria: lactobacilli to 100–104 CFU/ml, bifidobacteria to 105–108 CFU/ml, enterococci to 105–106 CFU/ml and typical E. coli to 103–106 CFU/ml, as well as an increase in the number of opportunistic microorganisms: Candida to 104–109 CFU/ml, hemolytic E. coli to 107–109 CFU/ml, Staphylococcus spp. to 104–106 CFU/ml, Klebsiella spp. and Enterobacter spp. to 106–108 CFU/ml. According to the degree of colonization of associative and conditionally pathogenic microbiota of the intestinal tract, significant fluctuations in the deviations of indicators were recorded in women and men with non-alcoholic steatohepatitis, alcoholic hepatitis and hepatitis C. Conclusions: the study revealed the significant imbalance of microbiome of the gastrointestinal tract: there was a tendency to increase the quantitative and qualitative indicators of the content of representatives of the opportunistic microbiota against the background of decreasing titers of symbiotic microorganisms. The most significant deviations in the composition of the intestinal microbiome were observed in patients with hepatitis C. The differences in the microbial landscape of the intestine of patients of different sex with liver diseases are shown, which was mentioned in the changing relationship of individual members of the intestinal microbiota